Inflammatory bowel disease among Bedouin Arabs in southern Israel. Issue 3 (March 2015) - Abu Freha, Naim; Schwartz, Doron; Elkrinawi, Jaber; Ben Yakov, Gil; Abu Tailakh, Muhammad; Munteanu, Daniela; Abu Ganim, Abdelrhman; Fich, Alexander
<x xml:space="preserve">Abstract</x> Background and aim Inflammatory bowel disease (IBD) has been associated with genetic and environmental factors, including urban living. IBD was rare in the Israeli Bedouin community 30 years ago. Over recent decades, a large proportion of this community has undergone a transition from a nomadic to a western lifestyle. Our aim was to carry out an updated evaluation of the clinical and epidemiological features of IBD in the Bedouin sector of southern Israel. Methods All Bedouin patients with a known diagnosis of Crohn's disease (CD) or ulcerative colitis (UC) were included in the retrospective study. Results The cohort included 31 CD patients and 31 UC patients. The mean age of the patients at diagnosis was 29±10.9 and 35±17.5 years for CD and UC, respectively. The prevalence rate for CD was 15.5/100 000 and the incidence rate was 0.8–3.55/100 000. Fourteen of the CD patients (45%) had ileal disease and 64.5% had inflammatory disease behavior according to the Montreal classification. Eleven of the CD patients (35%) were treated with anti-TNF-α and 26% had undergone surgery. Over the previous decade, the prevalence of UC was 14/100 000 and the incidence was 0.5–2.39/100 000. Eighteen UC patients (58%) had left-sided colitis. Three (9.7%) had undergone total colectomy for severe disease. Conclusion We found an increased prevalence of IBD in the Bedouin population, associated with their change in lifestyle over previous decades. However, the prevalence is still markedly lower than that in other population groups. A high percentage of patients were treated with anti-TNF-α and/or surgery.